2012
DOI: 10.2355/isijinternational.52.1054
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Delta Ferrite Content in Stainless Steel Castings

Abstract: The distribution of delta ferrite fraction was measured with the magnetic method in specimens of different stainless steel compositions cast by the investment casting (lost wax) process. Ferrite fraction measurements published in the literature for stainless steel cast samples were added to the present work data, enabling an extensive analysis about practical methods to calculate delta ferrite fractions in stainless steel castings. Nineteen different versions of practical methods were formed using Schaeffler, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 10 publications
0
19
1
5
Order By: Relevance
“…Martorano et al proposed that an increase in cooling rate caused a decrease in the content of residual ferrite. 36) The increase of nitrogen gas pressure not only affects the cooling rate in ingots, but also affects the nitrogen content in ingots. The content of residual ferrite firstly decreased and then increased with the increase of nitrogen gas pressure from 0.1 to 1.2 MPa.…”
Section: Effects Of Nitrogen Gas Pressure On the Microstructure Evolumentioning
confidence: 99%
“…Martorano et al proposed that an increase in cooling rate caused a decrease in the content of residual ferrite. 36) The increase of nitrogen gas pressure not only affects the cooling rate in ingots, but also affects the nitrogen content in ingots. The content of residual ferrite firstly decreased and then increased with the increase of nitrogen gas pressure from 0.1 to 1.2 MPa.…”
Section: Effects Of Nitrogen Gas Pressure On the Microstructure Evolumentioning
confidence: 99%
“…Essa metodologia foi a mesma empregada por Pardal e coautores [18] para determinar a fração volumétrica para um aço maraging 300.Os resultados obtidos por ambos os métodos foram comparados. A ferritoscopia geralmente é usada para medir a quantidade de fase ferromagnética, especialmente em aços inoxidáveis austeníticos, duplex e superduplex [30,31]. As medidas de ferritoscopia são baseadas no método da indução magnética [31] e apresentam uma similaridade de funcionamento com o instrumento usado por Habiby e coautores [22] para a detecção da austenita em um aço maraging 350.…”
Section: Materiais E Métodosunclassified
“…Addition of Ni can largely suppress the retainment of δferrite but it is expensive and it potentially shifts the martensite start (Ms) temperature below room temperature. Previous research demonstrated the influence of the chemical composition and cooling-rate on the retainment of δ-ferrite [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The phase distribution after solidification can be estimated by a variety of available models, such as the lever rule, the Scheil Model [23] and empirical models such as the Schaeffler diagram [21]. These models are easy to apply, but oversimplify the mechanisms during solidification and cooling to different degrees.…”
Section: Introductionmentioning
confidence: 99%